Comprehensive studies on the electrical transport of some chalcogenide semiconductors: frequency- and temperature-dependent AC conductivity - Ojha, Swarupa; Chamuah, Anil; Roy, Madhab; Bhattacharya, Sanjib (Frontiers in Physics, 2023)
The AC conductivity of chalcogenide semiconductors doped with Ag2S was extensively studied, not only for applications in devices but also for academic interests. X-ray diffraction studies reveal the presence of GeS, Ag2S, Se5.1S1.9, Se2.57S5.43, Ag2Se, S3Se5, Se4.7S3.3, and Ag8S nanocrystallites. The characteristic vibration that appeared in the range 500–600 cm−1 is due to the Ag–S bond, and the vibrations at 3,700 and 1600 cm−1 can be assigned as the bending and stretching vibrations of the O–H bond, which may be formed due to the adsorption of H2O molecules on the Ag2S surface. DC electrical conductivity can be increased by optical phonon frequency, which may be involved in the enhancement of structural vibrations. At low temperatures, the “density of states” increases from 3.337 × 1019 to 2.396 × 1021 eV−1 cm−3, and at high temperatures, it enhances from 3.417 × 1028 to 1.1356 × 1031 eV– 1 cm−3. The correlated barrier hopping model explores the maximum barrier height for composition, x = 0.1 as 0.0292 eV. The modified non-overlapping small polaron tunnelling model reveals the polaron transfer activation energy for x = 0.2 as 0.09110 eV. The independence of the electrical relaxation process of the system on temperature and its dependence on composition were exhibited by the scaling of the conductivity spectra.